Akar Gerakan Teologi Politik Fundamentalisme Islam Abad Modern Perspektif Karen Armstrong - Rohmatul Izad (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2018)
The article analyzes the root of political movement of Islamic fundamentalism in the modern era with particular focus on tracing theological and political reason of this group in Karen Armstrong's work. The author tries to critically discuss Armstrong's views about political ideology held by the Islamic fundamentalism. Since the Islamic fundamentalism needs to be carefully understood as a political movement, it can help us to clearly identify their position along with their ideological basis they fight for. This study concludes that various types and forms of what so-called